Etiologic agents of urinary tract infections in older adults from a health center of Carabobo state, Venezuela - Enza Capozzi; Davide Mobili Rocaro; Ana G. Kornett; María V. Perdomo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Urinary tract infections (UTI) are a common problem in medical practice, the etiology and susceptibility that produce the UTI may vary over time. It was conducted a study of no-experimental descriptive in order to detect the causative organisms of urinary tract infections and antimicrobial susceptibility in older adults residing in a health center of Carabobo state. They were evaluated 57 urine samples for bacteriological culture and the recovered microorganisms underwent susceptibility testing by disk diffusion method in agar (Kirby-Bauer). The most frequently isolated microorganisms in the ITU were Escherichia coli (53.84% and Klebsiella pneumoniae (15.40%), among others. In The antimicrobial susceptibility testing, the antibiotics that showed better antimicrobial activity were nitrofurantoin and amikacin (84.62%) each one, followed by gentamicin (76.92%) for all the Gramnegative bacilli recovered. The greater resistance was observed in ampicillin (61.54%), followed by trimethoprim-sulfamethoxazole (53.85%) and ciprofloxacin (46.15%), in enteric Gram-negative bacilli. In the present study was found a greater presence of Escherichia coli in the UTI as well as better antimicrobial activity of nitrofurantoin, amikacin and gentamicin against all the bacteria recovered.